Assessment of Small Bowel Motility and SMA Blood Flow Studied with Transabdominal Ultrasound - Nylund, Kim; Gjengstø, Andreas Jessen; von Volkmann, Hilde Løland; Gilja, Odd Helge (Ultrasound International Open, 2022)
Purpose Gastrointestinal ultrasound (GIUS) is a noninvasive imaging technique that may be used to study physiological changes in the small bowel. The aim of the study was to investigate the feasibility of measuring blood flow (BF) in the superior mesenteric artery (SMA) and regional motility in the small bowel with GIUS before and after a test meal and to compare ultrasound parameters to demographic factors such as age, sex, height, weight, and smoking habits.Materials and Methods 122 healthy volunteers aged 20 to 80 were examined after an overnight fast. Small bowel motility was registered in the upper left and lower right quadrants (ULQ and LRQ) with TUS and BF in the SMA with pulsed wave Doppler. The first 23 volunteers also received a 300 Kcal test meal and were re-examined 30 min postprandial.Results The feasibility of measuring BF was 97% in fasting patients while motility could be detected in 52% and 62% in the ULQ and LRQ, respectively. Females had a lower resistive index (RI) and a higher mean velocity than males, while the overall BF correlated with height. The RI had a negative correlation with age. Healthy volunteers with motility in the ileum were on average younger than those without motility. After the test meal, motility could be detected in the ULQ and LRQ in 95% and 90%, respectively, and the mean number of contractions in the ULQ increased significantly. As expected, there was a clear increase in all BF-parameters postprandially.Conclusion Regional motility in the small bowel was easier to detect after a test meal. There were some associations between demographic parameters and ultrasound parameters but overall the effects were relatively small.
Keywords: small bowel; blood flow; motility, THEMES; gastrointestinal ultrasound; healthy volunteers